Dose-specific childhood vaccine refusal in Balıkesir, Türkiye (2024): a population-based surveillance analysis - Keskin, Salih; Temizer, Mithat (The Turkish Journal of Pediatrics, 2026)
Background. Vaccine hesitancy has intensified since COVID-19. In Türkiye, a performance-based family medicine system provides free vaccines. Before May 2024, physicians could remove refusals from metrics tied to pay deductions, obscuring true rates. A new policy mandating documentation created a natural experiment. We used population-based data to quantify these previously hidden dose-specific refusal rates across the childhood schedule. Methods. We conducted a population-based ecological analysis of monthly dose-specific refusals among children aged 0–59 months in Balıkesir Province, in 2024. Refusals were extracted from Performance Exception Forms. Rates were calculated per 1,000 target children (Wilson 95% confidence intervals [CI]s), using populations derived from Turkish Statistical Institute counts. To quantify the policy’s impact, we fitted an interrupted time-series regression with a fixed breakpoint at May 2024. This model estimated the baseline level and slope (January-April) and compared them to the immediate level shift and new monthly slope post-reform (May–December). Results. Of 3,584 missed-dose exceptions, 3,002 (83.8%) were refusals. The aggregate refusal rate was 3.9 per 1,000 (January-April) versus 21.6 per 1,000 (May–December), while the rate of on-schedule vaccinations decreased from 99.3% to 97.5%. Segmented regression indicated a baseline of 2.6 per 1,000 and a post-policy level increase of 13.7 per 1,000 (p=0.005); pre- and post-policy monthly slopes were not significant. Refusals concentrated in booster and later-scheduled doses (18–48 months), whereas primary-series doses showed lower, comparatively stable rates. Notably, refusal for the second measles-mumps-rubella dose (MMR-II, 48 months) rose toward year-end, reaching 47.4 per 1,000 in December (95% CI, 35.1–63.6). Conclusions. Mandatory documentation exposed substantial under-ascertainment of parental refusal in performance-based records. Refusal is disproportionately clustered at booster and later-childhood visits, with MMR-II approaching herd-immunity margins. Programmatically, pediatric booster encounters are key leverage points for targeted counseling, and sustained, transparent surveillance as enabled by the new policy, is essential for early signal detection and response.